CEO narcissism: an upper echelons perspective on financial advisor involvement in M&A - Hoffmann, David Benedikt (2021)
This research examines the link between CEO narcissism and the engagement of financial advisors in M&A deals. Drawing on the definition and past findings of narcissistic CEOs conducting larger and more frequent M&As, this research expected that narcissistic CEOs would reduce the size of the financial advisor engagement and attempted to explore the moderators of this effect. In total, three hypotheses were tested on a sample of 157 deals. The results indicate that CEO narcissism can not explain the size of the financial advisor engagement. Never the less, for smaller deal sizes and longer process lengths, there seems to be an effect.